Green cities : an A-to-Z guide - Cohen, Nevin (Sage reference series on green society.)
This volume provides an overview of the key concepts that urban planners, policy makers, architects, engineers, and developers use to understand the sustainability dimensions of the urban environment. It identifies cities that have taken steps to become greener and discusses the strategies they have used; it also reviews broad concepts associated with green cities. The editors provide case studies of greener cities in order to discuss green urban design, infrastructure, and processes. It includes some 150 signed articles, photographs, hyperlinks, cross references, and a resource guide.